An Evaluation of Class Classification Strategies to Improve Qira’ah Skills: Stratifikasi Kelas dan Kemahiran Membaca Al-Qur'an di Ma'had Al-Jami'ah: Evaluasi Kualitatif - M. Jais Kaharudin; widiya yul; Riko Andrian (Language Development Center, 2025)
Background : Reading Arabic texts (Qira’ah) is a fundamental skill in Arabic language learning, particularly within Islamic higher education. However, diverse levels of student proficiency often result in learning gaps that hinder instructional effectiveness. To address this, class classification strategies based on initial Arabic ability have been introduced as a pedagogical innovation to enhance differentiated instruction and equitable learning outcomes. Objective: This study aims to critically evaluate the effectiveness of class classification strategies in improving students’ Qira’ah proficiency and to identify pedagogical factors that support or hinder the successful implementation of this approach. Method : This study employed a qualitative descriptive method, utilizing interviews and classroom observations as the primary tools for data collection. The participants consisted of eight Arabic language instructors and twenty students representing various proficiency levels. The data were analyzed thematically to identify patterns in learning experiences and instructional effectiveness across different class categories. Results and Discussion :The findings indicate that diagnostic assessments effectively support student placement, allowing instructional materials to align with learners’ linguistic readiness. Beginner students showed marked improvement in vocabulary mastery and comprehension, while advanced students benefited from authentic text engagement and analytical exercises. Nevertheless, limited class mobility and uneven progression across levels constrained the system’s overall effectiveness. Conclusion and Implications : Adaptive and context-based class classification strategies are essential to enhancing Qira’ah competence. The study recommends continuous formative assessment, mentoring systems involving peer tutors, and targeted teacher training to ensure sustainable improvement. These findings contribute to the development of more inclusive and responsive Arabic pedagogy in Islamic higher education.